Critical perspectives on economics of education - Mendolia, Silvia; O'Brien, Martin, 1957-; Paloyo, Alfredo; Yerokhin, Oleg (Abingdon, Oxon ; New York, NY : Routledge, 2022)
This book brings together leading scholars in the field to provide insights on economics of education. The book begins with an overview of education and human capacity development and looks at the production of education through individuals' learning, education financing, and the role of individual circumstances. It also analyses the complex relationship between education and mobility and highlights what key challenges for education systems in a global world are. Each chapter provides detailed analysis of interesting and policy-relevant topics in the fields of education economics and human capacity development. This book is a useful reference for those who wish to understand the changing landscape and models of higher education in the context of digital advances and innovation. It will also be of interest to those in the areas of education and training.
Keywords: Education -- Economic aspects; Education, Higher -- Finance; Postmodernism and higher education; Education -- Social aspects; BUSINESS & ECONOMICS / Education; EDUCATION / Adult & Continuing Education; EDUCATION / Educational Policy & Reform / General